2014
DOI: 10.1016/j.canlet.2013.11.014
|View full text |Cite
|
Sign up to set email alerts
|

LRH1 as a driving factor in pancreatic cancer growth

Abstract: Liver receptor homolog 1 (LRH1), directs the development and differentiation of embryonic pancreas, and is overexpressed in pancreatic cancer (PC). We hypothesized that LRH1 promotes PC growth. Cell proliferation and tumorigenicity in nude mice were compared between empty vector-transfected (control) and stable LRH1-overexpressed PC cell lines. The subsequent tumor burden, vasculature development, and histologic features were evaluated. LRH1 overexpression enhanced the expression of downstream target genes (cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 17 publications
0
47
0
Order By: Relevance
“…We prepared lentiviral mediated stable transfection of ASPH that localized to the cell surface in MIA PaCa2 cells (Fig. 1f) with very low endogenous levels of ASPH as described [7, 8]. Empty vector transfected cells served as the control.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We prepared lentiviral mediated stable transfection of ASPH that localized to the cell surface in MIA PaCa2 cells (Fig. 1f) with very low endogenous levels of ASPH as described [7, 8]. Empty vector transfected cells served as the control.…”
Section: Resultsmentioning
confidence: 99%
“…We established two stable MIA PaCa2 cell lines with overexpression of ASPH, and three stable AsPC-1 cell lines with knockdown of ASPH by specific shRNAs using the lentiviral system (GeneCopoeia, #EX-Z8758-Lv105 and # HSH011500-HIVU6, respectively) as described [7, 8]. Three shRNAs sequences used to target ASPH were as follows: [HSH011500-1-HIVU6 (OS217501)] cttctccatgaaatggtac, [HSH011500-2-HIVU6 (OS217502)] ctggaacctgaagtatctc, and ([HSH011500-3-HIVU6 (OS217503)] cctgaggataatcctgtag.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Similarly, LRH-1 is associated with pancreatic cancer initiation and metastasis, 15,53,54 suggesting potential for this nuclear receptor in the treatment of pancreatic cancer. Interestingly, LRH-1 has been proposed to play a dual role in pancreatic ductal adenocarcinoma (PDA), the most common type of pancreatic cancer.…”
Section: Future Directionsmentioning
confidence: 97%
“…57,58 Lin et al hypothesizes that LRH-1 is a driving factor that is shared between pancreatic embryogenesis and oncogenesis. 54 Of equal importance, recent studies have shown that LRH-1 can promote pancreatic cancer metastasis. 15,53 Pancreatic cancer cells originating from metastatic tumors have significantly higher expression of LRH-1 than in primary tumor cells.…”
Section: Prox1mentioning
confidence: 99%